2020
DOI: 10.1109/access.2020.2991034
|View full text |Cite
|
Sign up to set email alerts
|

Automating the ABCD Rule for Melanoma Detection: A Survey

Abstract: The ABCD rule is a simple framework that physicians, novice dermatologists and nonphysicians can use to learn about the features of melanoma in its early curable stage, enhancing thereby the early detection of melanoma. Since the interpretation of the ABCD rule traits is subjective, different solutions have been proposed in literature to tackle such subjectivity and provide objective evaluations to the different traits. This paper reviews the main contributions in literature towards automating asymmetry, borde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 95 publications
(119 reference statements)
0
14
0
Order By: Relevance
“…Tumor shape, whether spherical or elongated into an ellipsoid and quantified by a metric called eccentricity (15), is not usually measured nor currently considered in staging for PCa, unlike breast (16,17), lung (18,19), and skin (20,21) cancers. Recently, however, a study (15) showed that spherical prostate adenocarcinoma shape, rather than elongated, shows a propensity for higher Gleason score and presumed greater aggressiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Tumor shape, whether spherical or elongated into an ellipsoid and quantified by a metric called eccentricity (15), is not usually measured nor currently considered in staging for PCa, unlike breast (16,17), lung (18,19), and skin (20,21) cancers. Recently, however, a study (15) showed that spherical prostate adenocarcinoma shape, rather than elongated, shows a propensity for higher Gleason score and presumed greater aggressiveness.…”
Section: Introductionmentioning
confidence: 99%
“…However, this is not always the case as breast cancer patients with negative hormone receptor and positive HER2 expression show greater aggressiveness when they are more elongated and asymmetric (4). Similarly, in malignant melanomas (8,9), asymmetry in a tumor's shape may indicate its aggressiveness.…”
Section: Discussionmentioning
confidence: 99%
“…Staging components (1-3) such as intraprostatic tumor volumes/locations, metastatic extent, and lymph node involvement may indicate prostate tumor aggressiveness and provide important input for disease management. Tumor shape, whether spherical or elongated into an ellipsoid and quantified by a metric called eccentricity, is not usually measured and currently is not considered in staging for prostate cancer unlike breast (4,5), lung (6,7), and skin (8,9) cancers. Due to the relative absence of studies regarding tumor eccentricity in prostate cancer, definitive understanding of the relationship between tumor shape and potential cancer progression is limited and its contribution for assessing the prognosis of a patient is uncertain to date.…”
Section: Introductionmentioning
confidence: 99%
“…ABCDE 7 is widely adopted by the nondermatologists for extracting features from dermoscopic images than the Glasgow 7‐point checklist 8 during the clinical screening process 9 . A lesion is assigned a score(s) by the ABCD rule, a conjugation of the scores for four distinct features, like A‐symmetry, B‐order, C‐olors, and D‐ifferential structures 10 .…”
Section: Introductionmentioning
confidence: 99%